As percepções dos(as) técnico-administrativos(as) em educação sobre a jornada de trabalho de 30 horas semanais na Universidade Federal de Minas Gerais - Ligia Mara Sabino (2021)
This research investigates the perception of technical-administrative education on the impact of changing the working day from 40h to 30h weekly on the work processes and in the lives of these workers. The research was carried out with technician administrative (as) in education ufmg, Pampulha campus in the city of Belo Horizonte / MG, who make the 30h journey and with representatives of the union of the category. The methodology used were semi-structured interviews, analysis of documentary material (legal provisions, union documents, institutional offices) and bibliographic review. The analysis of the collected data was based on content analysis of Bardin (1979).The theoretical references are the studies of Ricardo Antunes (1995, 1999, 2003,2005) on the world of work, the researches of Helena Hirata (2002, 2007, 2008,2009) on the sexual division of labor, time as social construction, according to Elias (1998) and Teixeira (1998), the concept of experience in Bondía (2002) and Benjamin (1994) and the ergology of Yves Schwartz (2010), as well as studies on the impact of ethical-racial belonging on work , such as Gonzaga's research (2011) and Santos' studies(2018).The result of the research pointed out that the 30-hour journey caused changes in the experiences of technicians inside and outside the workplace: within the workplace, the TAEs gained greater autonomy in the organization of work processes and in the solution of the unpredictable work activity; outside the workplace, The TAEs gained more time to manage social obligations and perform activities without direct connection with work activity or indirectly related.Regarding the impact of the 30-hour journey in improving the quality of life, we saw that only the 30-hour journey does not provide such a guarantee, but is accompanied by other factors, such as staff hiring policy, public policies of urban mobility and change in the social imagination regarding the sexual and racial division of labor.The educational product of this research is a podcast. In the podcast were made available some perceptions of the technical-administrative in education about the 30-hour journey. The objective of the product is to disseminate the research results and provide a reflection on the reduction of the time dedicated to work within the possibilities of organization of work processes in the researched labor environment